Evaluate
( 4 4 + 6 4 ) ( 1 2 4 + 6 4 ) ( 2 0 4 + 6 4 ) ( 2 8 4 + 6 4 ) ( 3 6 4 + 6 4 ) ( 4 4 4 + 6 4 ) ( 5 2 4 + 6 4 ) ( 6 0 4 + 6 4 ) ( 8 4 + 6 4 ) ( 1 6 4 + 6 4 ) ( 2 4 4 + 6 4 ) ( 3 2 4 + 6 4 ) ( 4 0 4 + 6 4 ) ( 4 8 4 + 6 4 ) ( 5 6 4 + 6 4 ) ( 6 4 4 + 6 4 ) .
Details and Assumptions:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Sophie Germain Identity.
Wow nice question. Nice solution as well..
Sophie Germain.
Notice that all factors in both numerators and denominators can actually be written in the form of ( 4 4 . a 4 + 4 3 ) . For examples: ( 8 4 + 6 4 ) = ( ( 4 . 2 ) 4 + 6 4 ) = ( 4 4 . 2 4 + 4 3 ) . And also, ( 6 0 4 + 6 4 ) = ( ( 4 . 1 5 ) 4 + 6 4 ) = ( 4 4 . 1 5 4 + 4 3 ) .
So, changing all the factors, the question can be rewritten as : ( 4 4 . 1 4 + 4 3 ) ( 4 4 . 3 4 + 4 3 ) ( 4 4 . 5 4 + 4 3 ) . . . ( 4 4 . 1 3 4 + 4 3 ) ( 4 4 . 1 5 4 + 4 3 ) ( 4 4 . 2 4 + 4 3 ) ( 4 4 . 4 4 + 4 3 ) ( 4 4 . 6 4 + 4 3 ) . . . ( 4 4 . 1 4 4 + 4 3 ) ( 4 4 . 1 6 4 + 4 3 )
Notice that somehow, all factors in both numerators and denominators have the factor of 64= 4 3 (or you can say all factors are actually divisible by 64= 4 3 .
So, we divide all factors by 4 3 , and we get : ( 4 . 1 4 + 1 ) ( 4 . 3 4 + 1 ) ( 4 . 5 4 + 1 ) . . . ( 4 . 1 3 4 + 1 ) ( 4 . 1 5 4 + 1 ) ( 4 . 2 4 + 1 ) ( 4 . 4 4 + 1 ) ( 4 . 6 4 + 1 ) . . . ( 4 . 1 4 4 + 1 ) ( 4 . 1 6 4 + 1 )
The factors are actually written in form of 4 a 4 + 1 . The form is so uniform throughout all the factors, so it should have something special. After trying out some possibilities, we can actually know that : ( 4 a 4 + 1 ) = ( 2 a 2 + 2 a + 1 ) ( 2 a 2 − 2 a + 1 )
So for example, ( 4 . 2 4 + 1 ) = ( 2 . 2 2 + 2 . 2 + 1 ) ( 2 . 2 2 − 2 . 2 + 1 )
We change the fraction again into those factors, and we have : ( 2 . 1 2 + 2 . 1 + 1 ) ( 2 . 1 2 − 2 . 1 + 1 ) ( 2 . 3 2 + 2 . 3 + 1 ) ( 2 . 3 2 − 2 . 3 + 1 ) . . . ( 2 . 1 3 2 + 2 . 1 3 + 1 ) ( 2 . 1 3 2 − 2 . 1 3 + 1 ) ( 2 . 1 5 2 + 2 . 1 5 + 1 ) ( 2 . 1 5 2 − 2 . 1 5 + 1 ) ( 2 . 2 2 + 2 . 2 + 1 ) ( 2 . 2 2 − 2 . 2 + 1 ) ( 2 . 4 2 + 2 . 4 + 1 ) ( 2 . 4 2 − 2 . 4 + 1 ) . . . ( 2 . 1 4 2 + 2 . 1 4 + 1 ) ( 2 . 1 4 2 − 2 . 1 4 + 1 ) ( 2 . 1 6 2 + 2 . 1 6 + 1 ) ( 2 . 1 6 2 − 2 . 1 6 + 1 )
Notice that factors that follow the form of ( 2 a 2 + 2 a + 1 ) is always on the opposite sides of the fraction of ( 2 ( a + 1 ) 2 − 2 ( a + 1 ) + 1 ) , like for example : with a = 1 , the factor ( 2 . 1 2 + 2 . 1 + 1 ) is on the denominator , and with a = 1 , a + 1 = 2 , the factor ( 2 . 2 2 − 2 . 2 + 1 ) is on the numerator.
And also if the place is vice versa, it still holds; when a = 2 , the factor ( 2 . 2 2 + 2 . 2 + 1 ) is on the numerator, and with a = 2 , a + 1 = 3 , the factor ( 2 . 3 2 − 2 . 3 + 1 ) is on the denominator. So then I assumed that those factors will cancel out eachother, since each of them will be opposite to another.
Here's the proof : ( 2 a 2 + 2 a + 1 ) = ( 2 ( a + 1 ) 2 − 2 ( a + 1 ) + 1 )
2 a 2 + 2 a + 1 = 2 ( a 2 + 2 a + 1 ) − 2 a − 2 + 1
2 a 2 + 2 a + 1 = 2 a 2 + 4 a + 2 − 2 a − 2 + 1
2 a 2 + 2 a + 1 = 2 a 2 + 2 a + 1
So, after the cancellations of the same values of factors on both numerator and denominator are looked after, the remaining factor on the numerator should be the ( 2 a 2 + 2 a + 1 ) factor, with highest value of a possible, because the factor to cancel it must have higher a value, which is not exist in the question. So it should be a = 1 6 and the factor is : ( 2 . 1 6 2 + 2 . 1 6 + 1 ) = 5 4 5 .
While the factor left on the denominator should be ( 2 ( a + 1 ) 2 − 2 ( a + 1 ) + 1 ) factor with the lowest value of ( a + 1 ) possible, because the factor to cancel it must have lower value of a , which is not exist in the question. So it should be ( a + 1 ) = 1 and the factor is : ( 2 . 1 2 − 2 . 1 + 1 ) = 1 .
So, the final fraction after the cancellation would be : 1 5 4 5 At last, the final answer is 5 4 5 .
We first factor out 2 6 from each of the terms. This leaves us with
∏ i = 1 8 4 ⋅ ( 2 i − 1 ) 4 + 1 ∏ i = 1 8 4 ⋅ ( 2 i ) 4 + 1
The general form of all these expressions is 4 ⋅ x 4 + 1 . This can be factored out into ( 2 ( x 2 ) − 2 x + 1 ) × ( 2 ( x 2 ) + 2 x + 1 ) . Observe that 2 ( x + 1 ) 2 − 2 ( x + 1 ) + 1 = 2 x 2 + 4 x + 2 − 2 x − 2 + 1 = 2 x 2 + 2 x + 1 . Hence, we get that the product is equal to
[ ∏ n = 1 8 2 ( 2 n − 1 ) 2 − 2 ( 2 n − 1 ) + 1 ] [ ∏ n = 1 8 2 ( 2 n − 1 ) 2 + 2 ( 2 n − 1 ) + 1 ] [ ∏ n = 1 8 2 ( 2 n ) 2 − 2 ( 2 n ) + 1 ] [ ∏ n = 1 8 2 ( 2 n + 1 ) 2 − 2 ( 2 n + 1 ) + 1 ] = ∏ n = 1 1 6 2 ( k ) 2 − 2 ( k ) + 1 ∏ k = 2 1 7 2 ( k ) 2 − 2 ( k ) + 1
As such, this product telescopes, and we obtain 2 ( 1 ) 2 − 2 ( 1 ) + 1 2 ( 1 7 ) 2 − 2 ( 1 7 ) + 1 = 5 4 5 .
[Edits for clarity - Calvin]
I bashed using a calculator :P
Let's define f ( x ) = x 4 + 6 4 . We can factor f(x) like this: f ( x ) = ( x 2 − 4 x + 8 ) ( x 2 + 4 x + 8 ) . Since all numbers in the expression taken to the fourth power are divisible by 4, we will make use of the function g(y) = f(4y). Then g ( y ) = ( ( 4 y ) 2 − 4 ( 4 y ) + 8 ) ( ( 4 y ) 2 + 4 ( 4 y ) + 8 ) = = 6 4 ( 2 y 2 − 2 y + 1 ) ( 2 y 2 + 2 y + 1 ) .
Let's define h ( y ) = 2 y 2 − 2 y + 1 . Evaluating h ( y + 1 ) , we get 2 y 2 + 2 y + 1 , which is the second nonconstant factor in the expression for g(y), so g ( y ) = 6 4 h ( y ) h ( y + 1 ) .
Thus, the expression we are asked to evaluate is g ( 1 ) g ( 3 ) g ( 5 ) g ( 7 ) g ( 9 ) g ( 1 1 ) g ( 1 3 ) g ( 1 5 ) g ( 2 ) g ( 4 ) g ( 6 ) g ( 8 ) g ( 1 0 ) g ( 1 2 ) g ( 1 4 ) g ( 1 6 ) = = 6 4 8 h ( 1 ) h ( 2 ) h ( 3 ) h ( 4 ) h ( 5 ) h ( 6 ) h ( 7 ) h ( 8 ) h ( 9 ) h ( 1 0 ) h ( 1 1 ) h ( 1 2 ) h ( 1 3 ) h ( 1 4 ) h ( 1 5 ) h ( 1 6 ) 6 4 8 h ( 2 ) h ( 3 ) h ( 4 ) h ( 5 ) h ( 6 ) h ( 7 ) h ( 8 ) h ( 9 ) h ( 1 0 ) h ( 1 1 ) h ( 1 2 ) h ( 1 3 ) h ( 1 4 ) h ( 1 5 ) h ( 1 6 ) h ( 1 7 ) = h ( 1 ) h ( 1 7 ) = 5 4 5 .
I just calculated first 2 pairs of fractions and got 13/1, 41/13 respectively. Then, I noticed 1+(4+8)=13 and 13+(12+16)=41. Then I just kept writing rest of the pairs in this way and got 545.
(13/1).(41/13).(85/41).(145/85).(221/145).(313/221).(421/313).(545/421) = 545
We can use Texas Instruments Calculator as below.
- 6 store X
1 ENTER
A
N
S
s
t
o
r
e
A
:
X
+
8
s
t
o
r
e
X
:
A
∗
(
(
X
+
2
)
4
+
6
4
)
/
(
(
X
−
2
)
4
+
6
4
)
Press ENTRY eight times we get 545
..(for ANS, ENTRY we have to use 2nd key, for A , and : the ALPHA key)
What has maths taught you? Using the calculator for cheating. You are supposed to evaluate not press on the calculator.
Log in to reply
Thanks for your compliments! I have given an algorithm for solving such problem. Solution in brilliant has also been by graphing calculators and the graphs are posted with the solution.
[(8^4+64)(16^4+64)(24^4+64)(32^4+64)(40^4+64)(48^4+64)(56^4+64)(64^4+64)] / [(4^4+64)(12^4+64)(20^4+64)(28^4+64)(36^4+64)(44^4+64)(52^4+64)(60^4+64)]
Please use L A T E X
Problem Loading...
Note Loading...
Set Loading...
x 4 + 6 4 = ( x 2 + 8 ) 2 − 1 6 x 2 = ( x 2 − 4 x + 8 ) ( x 2 + 4 x + 8 ) = ( ( x − 2 ) 2 + 4 ) ( ( x + 2 ) 2 + 4 ) .
So the product is equal to ( 2 2 + 4 ) ( 6 2 + 4 ) ( 1 0 2 + 4 ) ( 1 4 2 + 4 ) … ( 5 8 4 + 4 ) ( 6 2 2 + 4 ) ( 6 2 + 4 ) ( 1 0 2 + 4 ) ( 1 4 2 + 4 ) ( 1 8 2 + 4 ) … ( 6 2 2 + 4 ) ( 6 6 2 + 4 ) . Thus the product telescopes (terms cancel out) and we obtain 2 2 + 4 6 6 2 + 4 = 5 4 5 .